Proceedings of the Conference on Topical Research in Accounting (Book). - Murdock, Richard J.; Dominiak, Gere (The Accounting Review, 1977)
Abstract Reviews the book 'Proceedings of the Conference on Topical Research in Accounting,' edited by Michael Schiff and George Sorter.